2020
DOI: 10.1111/jan.14341
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric clinical and social concerns identified by home visit nurses in the immediate postdischarge period

Abstract: Aim:To describe paediatric postdischarge concerns manifesting in the first 96 hr after hospital discharge.Design: Analysis of nursing documentation generated as part of a randomized controlled trial evaluating the effect of a nurse home visit on healthcare re-use. Methods:We analysed home visit records of 651 children (age <18) hospitalized at a large Midwestern children's hospital in 2015 and 2016 who were enrolled in the trial.Registered nurses documented concerns in structured fields and free-text notes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…In line with the literature (18) , it is observed that medication administration errors are among the main adverse events after hospital discharge. A recent study conducted in the United States with caregivers of pediatric patients after hospital discharge found medication safety as the main concern of the nursing team during home visits, with the main problems being those related to family administration of drugs and medication reconciliation (18) .…”
Section: Discussionsupporting
confidence: 80%
“…In line with the literature (18) , it is observed that medication administration errors are among the main adverse events after hospital discharge. A recent study conducted in the United States with caregivers of pediatric patients after hospital discharge found medication safety as the main concern of the nursing team during home visits, with the main problems being those related to family administration of drugs and medication reconciliation (18) .…”
Section: Discussionsupporting
confidence: 80%
“…When considering that professionals working in PHC must be prepared to assist children and contribute to the qualified care, as well as to the protection and promotion of the health of this clientele (Tubbs-Cooley et al, 2020;Silva et al, 2018), this research aimed to identify components that interfere in the practice of NC to the NB in PHC.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 If home visits are not ultimately a solution to pediatric reutilization reduction, they may nonetheless still enable families to effectively manage the concerns that families endorse following discharge, including medication safety and social hardships. 8 In summary, Riddle et al not only provided important context for the unexpected outcome of a well-designed randomized clinical trial but also provided a rich source of qualitative data that furthers our understanding of a child's discharge home from the hospital through the perspective of multiple stakeholders. While the authors offer well-reasoned next steps in narrowing the intervention population of interest and enhancing connections of families with PCP care, it may be time to broadly revisit postdischarge interventions and outcomes to identify new approaches and redefine quality measures for hospital-to-home transitions of children and their families.…”
mentioning
confidence: 99%
“…In contrast to the increasing presence of hospital reimbursement penalties among state Medicaid agencies for readmissions, a shift in focus toward outcome measures that are patient‐ and family‐centered is imperative 1,7 . If home visits are not ultimately a solution to pediatric reutilization reduction, they may nonetheless still enable families to effectively manage the concerns that families endorse following discharge, including medication safety and social hardships 8 …”
mentioning
confidence: 99%